Lapatinib plus Letrozole as First-Line Therapy for HER-2(+) Hormone Receptor–Positive Metastatic Breast Cancer - Schwartzberg, Lee S. (AlphaMed Press, 2010)
OBJECTIVE. To evaluate the efficacy and tolerability of letrozole plus lapatinib versus letrozole plus placebo in women with hormone receptor (HR)(+) human epidermal growth factor receptor (HER)-2(+) tumors receiving first-line therapy for metastatic breast cancer (MBC). PATIENTS AND METHODS. Postmenopausal women (n = 1,286) with HR(+) MBC were randomized to daily oral treatment with letrozole (2.5 mg) plus lapatinib (1,500 mg) versus letrozole (2.5 mg) plus placebo. Of the 1,286 patients enrolled in the phase III study, 219 had HER-2(+) tumors. The primary endpoint was progression-free survival (PFS) in HER-2(+) patients. RESULTS. Results in the HR(+) HER-2(+) population (n = 219) are presented. The addition of lapatinib to letrozole resulted in a significantly lower risk for disease progression than with letrozole alone (hazard ratio, 0.71; 95% confidence interval, 0.53–0.96). The PFS time was 8.2 months, versus 3.0 months. The objective response rate (ORR) (28% versus 15%) and clinical benefit rate (CBR) (48% versus 29%) were also significantly greater in lapatinib-treated women. The most common adverse events in the lapatinib group were diarrhea (68%) and rash (46%), primarily grade 1 and 2. CONCLUSIONS. The addition of lapatinib to letrozole is well tolerated and leads to a significantly greater PFS time, ORR, and CBR than with letrozole alone in women with MBC who coexpress HR and HER-2.